Fine‐Scaled Piezoelectric Ceramic/Polymer 2‐2 Composites for High‐Frequency Transducer. Issue 4 (23rd February 2014) - Zhang, Ye; Jiang, Yun; Lin, Xiujuan; Xie, Rui; Zhou, Kechao; Button, Tim W.; Zhang, Dou; Kim, H.‐E.
<x xml:space="preserve">Abstract</x> A novel technique was utilized to fabricate fine‐scaled piezoelectric ceramic/polymer 2‐2 composites for high‐frequency ultrasonic transducers. Lead zirconate titanate (PZT) was used as raw material. Tape‐casted acetylene black tapes were used to define kerfs after sintering. A one‐directional supporter was utilized to avoid distortion of PZT elements. PZT elements with 20 ± 2 μm width exhibited good consistency in longitudinal direction. A resonant method was utilized to evaluate the piezoelectric and dielectric properties of the composites. A 72‐μm‐thick composite with an aspect ratio of 3.6 exhibited a kt of 0.61 with satisfied piezoelectric and dielectric properties. A prototype high‐frequency ultrasonic transducer was fabricated and evaluated by an underwater pulse‐echo test. The center frequency was found to be 23.75 MHz, with −6 dB bandwidth of 5.5 MHz.